PEMBINAAN MANAJERIAL BAGI PENGELOLAAN SEKOLAH WIRAUSAHA ‘AISYIYAH (SWA) KABUPATEN PEKALONGAN - Chalimah Chalimah (LPPM Universitas Pekalongan, 2020)
Managerial guidance for operating “Wirausaha “Aisyiyah School”(SWA), for making professionality in SWA and build good coordination between all organisation structure. SWA build for helping to the poor people and using commitment in productive sector in economy as well as to get economic stabilisation for woman. SWA in Kabupaten Pekalongan was the first SWA ever build in Central Java Province. Almost 3 years the head of Aisyiyah branch pekalongan did not have commitment to gain SWA program, advantage and responsibility. The output target from this activity is to reform and to manage SWA in operation concept to become more professional which guidance with 4 management function consist of: planning, organizing, moving, supervising. We have using purposing discuss and workshop methodz. From this two in front, will be using for making reconstruction in SWA guidance which covering organisation structure in regional branch to do their job as well as on all procedure. Beside it, MEKPDA will give mentoring toruling the coordination in order with PCA under consideration with SWA.